THE INFLUENCE OF E-WOM, BRAND AWARENESS AND PERCEIVED QUALITY ON GEN Z’S PURCHASE INTENTION FOR MOMENT SELF PHOTO STUDIO MANADO SERVICES - Pahaganas, Michelle; Gunawan, Emilia.M; Rumokoy, Lawren.J (Universitas Sam Ratulangi, 2025)
This study aims to analyse the influence of e-wom, brand awareness and perceived quality for moment self photo studio Manado services, one of the popular self service photo studio. The independent variables in this study are E-WOM, Brand Awareness and Perceived Quality, while the dependent variables analysed is Purchase Intention. This research uses a quantitative method with a sample of 100 respondents who are Generation Z and active TikTok users. Data was collected through a questionnaire with a Likert scale. The results of this study indicate that E-WOM, Brand Awareness, and Perceived Quality simultaneously shows positive and significant effect on Gen Z's Purchase Intention. The implementing of interactive E-WOM, innovative strategies on Brand Awareness and increased Perceived Quality is proven to play an important role in increasing purchase intention. Keywords: E-WOM, Brand Awareness, Perceived Quality and Purchase Intention